SOCIALIZATION ON PREVENTING THE SPREAD OF HOAX NEWS IN ONLINE NEWS MEDIA AT GROGOL VILLAGE, WERU, SUKOHARJO - Wijayanto, Danar Susilo; Kusumawati, Wahyu (Pusat Penelitian dan Pengabdian Masyarakat, 2025)
The socialization activity on hoax news in Grogol Village, Weru Subdistrict, Sukoharjo Regency, was conducted to increase public awareness about the dangers of hoax news and ways to prevent it. Using a community education approach, the team provided education on the definition, characteristics, and risks of hoax news, as well as how to protect themselves from the spread of fake news. This activity involved hands-on practice of checking the truth of the news using the website cekhoaks.id and promoting the habit of